Suicide risk assessment fears, attitudes and behaviours of lifeline crisis supporters. (1st August 2022) - Hawgood, Jacinta; Spafford, Sarah G.; Evans, Ann; Webster, Amy; Koo, Yu Wen
Abstract: Lifeline Australia operates crisis support services through Lifeline Crisis Supporters. An integral part of their role is to conduct online suicide risk assessments with help‐seekers. However, there is limited literature regarding suicide risk assessment practices for this population. This study aimed to examine how suicide prevention training, vicarious trauma and fears impacted suicide risk assessment behaviours of Lifeline Crisis Supporters. A cross‐sectional survey design was used to recruit a volunteer convenience sample of 125 Lifeline Australia Crisis Supporters (75.2% females; M age  = 54.9) in 2018 to participate in an online survey. Findings revealed that those with more suicide‐specific training had less risk assessment‐related fears, and that fears were not related to attitudes towards suicide prevention. There was no significant relationship between vicarious trauma and amount of training or years of experience in the role. Further, participants with higher levels of vicarious trauma demonstrated significantly more negative attitudes towards suicide prevention. Overall, training appears to be a significant factor in suicide risk assessment practice behaviours of Lifeline Crisis Supporters, highlighting a need for ongoing training and support for them. This research also suggests that whilst fears exist, they do not significantly impair Lifeline Crisis Supporters' ability to undertake suicide risk assessment.